A PERANAN ISTRI TERHADAP PENDAPATAN RUMAH TANGGA NELAYAN DAN CURAHAN WAKTU PRODUKTIF DI DESA PASIR MAYANG KECAMATAN KUARO KABUPATEN PASER: PERANAN ISTRI TERHADAP PENDAPATAN RUMAH TANGGA NELAYAN DAN CURAHAN WAKTU PRODUKTIF - Ela, Mutiara; Saleha, Qoriah; Darmansyah, Oon (2339-1324, 2024)
The study's objectives were to know the working time and contribution of Fisherman’s wife to increase the family income. The study was conducted in Pasir Mayang Village with 30 Fisherman’s wife as respondents using by stratified random sampling method. The results showed that respondents' average working time for domestic activities was 5 hours 36 minutes daily. The mean working time of respondents for productive activities was 7 hours 3 minutes daily. Daily personal and leisure activities were 11 hours 45 minutes and 2 hours 24 minutes, respectively. Moreover, social activities were 41 minutes. The contribution of the Fisherman's wife is 34.71%, which means that she is able to contribute an income of Rp 1.082.569,44/month to the income of the Fisherman's family.